2016
DOI: 10.1111/epi.13486
|View full text |Cite
|
Sign up to set email alerts
|

The progression of electrophysiologic abnormalities during epileptogenesis after experimental traumatic brain injury

Abstract: Summary Objective Posttraumatic epilepsy (PTE) accounts for 20% of acquired epilepsies. Experimental models are important for studying epileptogenesis. We previously reported that repetitive high-frequency oscillations with spikes (rHFOSs) occur early after lateral fluid percussion injury (FPI) and may be a biomarker for PTE. The objective of this study was to use multiple electrodes in rat hippocampal and neocortical regions to describe the long-term electroencephalographic and behavioral evolution of rHFOSs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 30 publications
4
76
0
Order By: Relevance
“…Therefore, an epilepsy prevention trial could possibly be successfully conducted within a reasonable follow‐up period of a few years. A recent study of a fluid percussion injury model of traumatic brain injury in rats found that animals with repetitive high‐frequency oscillations with spikes were at very high risk of developing late spontaneous focal seizures . The repetitive nature of these spikes associated with high‐frequency oscillations in this animal model of epileptogenesis, when extrapolated to humans, may be analogous to the LPDs noted among our study population.…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, an epilepsy prevention trial could possibly be successfully conducted within a reasonable follow‐up period of a few years. A recent study of a fluid percussion injury model of traumatic brain injury in rats found that animals with repetitive high‐frequency oscillations with spikes were at very high risk of developing late spontaneous focal seizures . The repetitive nature of these spikes associated with high‐frequency oscillations in this animal model of epileptogenesis, when extrapolated to humans, may be analogous to the LPDs noted among our study population.…”
Section: Discussionsupporting
confidence: 74%
“…In rats with spontaneous seizures, the average seizure severity was Racine score 3.37 ± 0.18 (range, 3–4), and average seizure duration was 97.88 ± 10.20 seconds (range, 50–140 seconds), confirming the risk for post‐traumatic epileptogenesis in the experimental model. It is possible that strain differences, use of younger juvenile rats, which are more susceptible to adverse effects of brain injury, implementation of injury on the day after surgery to minimize neuroprotection due to surgical anesthesia, and inclusion criteria based on apnea duration contributed to greater proportion of rats developing spontaneous seizures compared to earlier studies …”
Section: Resultsmentioning
confidence: 99%
“…It is possible that strain differences, use of younger juvenile rats, which are more susceptible to adverse effects of brain injury, 40 implementation of injury on the day after surgery to minimize neuroprotection due to surgical anesthesia, and inclusion criteria based on apnea duration contributed to greater proportion of rats developing spontaneous seizures compared to earlier studies. [41][42][43] To transition our findings on TLR4 modulation of excitability in ex vivo slices to in vivo, we examined whether systemic TLR4 antagonism could modify dentate excitability 1 week after injury. Sham and FPI rats were treated with CLI-095 (0.5mg/kg, subcutaneously, for 3 days) starting 20 to 24 hours after injury, and dentate excitability was examined in hippocampal slices 6 to 8 days later.…”
Section: Systemic Tlr4 Antagonism In Vivo Has Opposing Effects On Earmentioning
confidence: 99%
“…) increases with age . Additionally, patterns that have been interpreted by the authors of these studies as spike‐wave discharges (SWDs) have been reported in experimental controls in many strains (see Table ) Recommendation: Report strain, age, sex, and vendor of the animals, because all of these may influence the onset and frequency of SWDs (Table ). …”
Section: Methodological Considerationsmentioning
confidence: 99%